2018
DOI: 10.1038/s41418-018-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

p73 coordinates with Δ133p53 to promote DNA double-strand break repair

Abstract: Tumour repressor p53 isoform Δ133p53 is a target gene of p53 and an antagonist of p53-mediated apoptotic activity. We recently demonstrated that Δ133p53 promotes DNA double-strand break (DSB) repair by upregulating transcription of the repair genes RAD51, LIG4 and RAD52 in a p53-independent manner. However, Δ133p53 lacks the transactivation domain of full-length p53, and the mechanism by which it exerts transcriptional activity independently of full-length p53 remains unclear. In this report, we describe the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 58 publications
(65 reference statements)
3
63
0
Order By: Relevance
“…In the present study, we report that the AMPK‐Mfn1 pathway is closely regulated by resveratrol . This finding provides an easy and effective approach to activate protective the AMPK‐Mfn1 pathway in the setting of cerebral IR injury …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the present study, we report that the AMPK‐Mfn1 pathway is closely regulated by resveratrol . This finding provides an easy and effective approach to activate protective the AMPK‐Mfn1 pathway in the setting of cerebral IR injury …”
Section: Discussionsupporting
confidence: 63%
“…74,75 This finding provides an easy and effective approach to activate protective the AMPK-Mfn1 pathway in the setting of cerebral IR injury. 76…”
Section: Discussionmentioning
confidence: 99%
“…Δ133p53 works together with the p53 gene family member p73 to join the promoters of all three repair genes Ligase4, Rad51, and Impact of Δ133p53 on the chemosensitivity K. Liu and J. Lin Rad52. Δ133p53, which cooperates with p73, acts synergistically to promote the expression of Rad51, Rad52, and Ligase4 and the repair of damaged DNA in various cancer cells Gong et al, , 2018. In this study, Δ133p53 reduced the sensitivity of H1299 to the chemotherapeutic drugs, due to which DNA of the cell line H1299 was injured.…”
Section: Discussionmentioning
confidence: 57%
“…Δ133p53 works together with the p53 gene family member p73 to join the promoters of all three repair genes Ligase4, Rad51, and Rad52. Δ133p53, which cooperates with p73, acts synergistically to promote the expression of Rad51, Rad52, and Ligase4 and the repair of damaged DNA in various cancer cells (Gong and Chen, ; Gong et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al (74) found that D133p53 binds to DNp63 and utilizes its TA domain to promote glycolytic metabolism, leading to cancer cell proliferation. Additionally, p73 and D133p53 act synergistically to promote the expression of RAD51, LIG4, and RAD52 by binding to a region containing a D133p53-responsive element and a p73-responsive element in the promoters of all 3 DNA double-strand break repair genes (75). Figure 9.…”
Section: Discussionmentioning
confidence: 99%